Suspected myocardial necrosis in farmed Atlantic salmon, Salmo salar L. a field case - Poppe, T T (Journal of fish diseases, 2007)
Arteriosclerosis of the coronary artery has been described as a 'fact of life' for Pacific and Atlantic salmonids due to the high prevalence in spawning fish. The lesions are believed to be the result of overstretching of the highly distensible bulbus arteriosus whereby the endothelium of the main coronary vessel becomes mechanically damaged and a smooth muscle proliferation ensues with resultant partial occlusion of the vessel. The physiological significance for the function of the heart has yet to be demonstrated, but experimental studies show that, for example, swimming performance is compromised in fish in which the coronary artery has been ligated. This paper describes a case of myocardial necrosis in harvest-size Atlantic salmon during and after transportation to the slaughterhouse. Mortality during this process reached 10% in some of the transports and affected fish showed characteristic signs of congestive cardiac failure. Histology revealed extensive myointimal proliferation in the coronary artery and patchy necrosis of the compact ventricular myocardium. Several unfavourable factors such as high water temperature, skeletal malformations and crowding all probably contributed to extra cardiac workload. To the best of our knowledge, this is the first reported field case showing a link between coronary lesions and severe cardiac pathology